2023
DOI: 10.17305/bb.2022.8549
|View full text |Cite
|
Sign up to set email alerts
|

Sivelestat sodium attenuates acute lung injury by inhibiting JNK/NF-κB and activating Nrf2/HO-1 signaling pathways

Abstract: Sivelestat sodium (SIV), a neutrophil elastase inhibitor, is mainly used for the clinical treatment of acute respiratory distress syndrome (ARDS) or acute lung injury (ALI). However, studies investigating the effects of SIV treatment of ALI are limited. Therefore, this study investigated the potential molecular mechanism of the protective effects of SIV against ALI. Human pulmonary microvascular endothelial cells (HPMECs) were stimulated with tumor necrosis factor α (TNF-α), and male Sprague-Dawley rats were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 46 publications
(48 reference statements)
1
9
0
Order By: Relevance
“…Remarkably, treatment with sivelestat led to a marked improvement in these kidney structural parameters. The observed effects of sivelestat in attenuating oxidative stress and restoring the pathological injury, as shown in the present study, is supported by the findings of Zhang et al [ 16 ]. In their study, the authors showed that sivelestat effectively mitigates acute lung injury, reducing the levels of inflammatory factors, ROS and MDA, while increasing the levels of SOD and GSH-Px in lung tissues, potentially via the molecular mechanisms of JNK/NF-κB activation and Nrf2/HO-1 signaling pathway inhibition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Remarkably, treatment with sivelestat led to a marked improvement in these kidney structural parameters. The observed effects of sivelestat in attenuating oxidative stress and restoring the pathological injury, as shown in the present study, is supported by the findings of Zhang et al [ 16 ]. In their study, the authors showed that sivelestat effectively mitigates acute lung injury, reducing the levels of inflammatory factors, ROS and MDA, while increasing the levels of SOD and GSH-Px in lung tissues, potentially via the molecular mechanisms of JNK/NF-κB activation and Nrf2/HO-1 signaling pathway inhibition.…”
Section: Discussionsupporting
confidence: 92%
“…Sivelestat is a selective inhibitor of neutrophil elastase (NE), which has been proved to reduce lung injury [ 12 , 13 ], systemic inflammatory response syndrome [ 14 ], and acute respiratory distress syndrome [ 14 ]. Other evidence shows that sivelestat can improve the survival rate of septic animals and reduce sepsis-related lung injury [ 15 , 16 ]. By a mouse models of ischemic AKI, a significant increase in NE expression in the renal cortex/proximal tubules was observed [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although NF-κB and MPO are frequently co-assayed in research related to ALI/ARDS and ECs, direct evidence confirming whether NF-κB explicitly regulates MPO expression or activity is currently lacking ( Mao and Wu, 2022 ). Other key factors like “HO-1”, “VEGF/VEGFA”, and “STAT3/STAT5” are also related to NF-κB in ECs and ALI/ARDS research ( Huang et al, 2019 ; Zhang H. et al, 2023 ; Chang and Zhang, 2023 ). Despite these observed interactions in various studies, the intricate mechanisms and interplays remain a focus for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Sivelestat sodium, a neutrophil elastase inhibitor, has shown promising results to attenuate ARDS [6]. The mechanism of sivelestat includes inhibition of nuclear factor-kappa B (NF-κB) activation, reduction of reactive oxygen species (ROS) production, and modulation of the Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway [7]. These effects contribute to the suppression of proin ammatory cytokines and chemokines which are key mediators of ARDS pathogenesis [8].…”
Section: Introductionmentioning
confidence: 99%